2012
DOI: 10.1111/j.1365-2486.2012.02778.x
|View full text |Cite
|
Sign up to set email alerts
|

The costs of keeping cool in a warming world: implications of high temperatures for foraging, thermoregulation and body condition of an arid‐zone bird

Abstract: Recent mass mortalities of bats, birds and even humans highlight the substantial threats that rising global temperatures pose for endotherms. Although less dramatic, sublethal fitness costs of high temperatures may be considerable and result in changing population demographics. Endothermic animals exposed to high environmental temperatures can adjust their behaviour (e.g. reducing activity) or physiology (e.g. elevating rates of evaporative water loss) to maintain body temperatures within tolerable limits. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
328
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(340 citation statements)
references
References 52 publications
11
328
1
Order By: Relevance
“…Despite summer diurnal temperatures often exceeding 358C, nocturnal temperatures are frequently below 108C in the southern Kalahari Desert, especially during dry periods when re-radiation levels are high at night. By allowing T b to decrease with T air , desert birds would conserve energy on cool nights, which may offset diurnal reductions in foraging performance brought about by low food availability and/or high T air (du Plessis et al 2012). Daily heterothermy levels in semi-desert birds, on the other hand, showed a stronger relationship to T air during the dry season than during the wet season.…”
Section: Fig 5 Daily Heterothermy Index (Hi)mentioning
confidence: 95%
See 1 more Smart Citation
“…Despite summer diurnal temperatures often exceeding 358C, nocturnal temperatures are frequently below 108C in the southern Kalahari Desert, especially during dry periods when re-radiation levels are high at night. By allowing T b to decrease with T air , desert birds would conserve energy on cool nights, which may offset diurnal reductions in foraging performance brought about by low food availability and/or high T air (du Plessis et al 2012). Daily heterothermy levels in semi-desert birds, on the other hand, showed a stronger relationship to T air during the dry season than during the wet season.…”
Section: Fig 5 Daily Heterothermy Index (Hi)mentioning
confidence: 95%
“…Desert birds are exposed to these T air fluctuations to a greater degree than taxa such as reptiles and small mammals because few diurnal avian species make use of thermally buffered microsites below ground (Bartholomew and Cade 1963, Wolf 2000. Limited food resources often force desert birds to forage during hot weather (Tieleman and Williams 2002), posing the potential risk of water and energy expenditure rates exceeding intake rates (du Plessis et al 2012). Moreover, the scarcity of surface water means that balancing water losses associated with high rates of thermoregulatory EWL may become costly during periods of very hot weather.…”
Section: Introductionmentioning
confidence: 99%
“…In the few studies demonstrating fitness costs of high temperatures, negative effects on body condition and survival are associated with air temperatures more than or equal to 358C [3][4][5]7]. Studies of physiology show that for many passerines, the onset of panting, which facilitates evaporative cooling, occurs at slightly lower temperatures, at about 308C, but only when air temperatures approach body temperature (approx.…”
Section: Direct Effects Of Climate On Survivalmentioning
confidence: 99%
“…Prolonged exposure (i.e. over successive days) to high temperatures in the mid-30s8C can lead to reductions in adult body mass, as well as affect nestling development, presumably through a combination of dehydration via increased rates of evaporative cooling and energetic constraints that result from reduced foraging opportunities or provisioning effort [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For tropical species at lower air temperatures and higher humidity the thermal endpoints may be significantly lower (Weathers, 1997). Studies of wild birds in arid habitats have identified important threshold T a values in the 30-40°C range for variables related to body condition (du Plessis et al, 2012) and provisioning rates during breeding (Cunningham et al, 2013), suggesting that in many cases, detailed models of specific determinants of survival and/or reproduction will be necessary to predict the effects of climate change. However, catastrophic mortality events during extreme heat waves in the arid zones of Australia and elsewhere (reviewed by McKechnie et al, 2012;McKechnie and Wolf, 2010), combined with predicted increases in the frequency and intensity of heat waves (IPCC, 2011), underscore the relevance of models of avian survival over time scales of hours during acute heat exposure, and the need for comparative data on the upper limits of avian heat tolerance.…”
Section: Scaling Of Heat Tolerancementioning
confidence: 99%